2011
DOI: 10.1097/mph.0b013e31821b0770
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Hydroxyurea in Providing Transfusion Independence in β-Thalassemia

Abstract: HU was found to be safe in patients with β-thalassemia major, and resulted in the reduction of transfusion requirement and in an increase in the interval between transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 13 publications
2
40
0
Order By: Relevance
“…67,74,104 No renal or hepatic side effects were reported with hydroxyurea therapy. 67,69,71,74,75,82,85 Although some reports suggested that hydroxyurea may adversely affect gonadal function, 87 others failed to document such an association even on long-term therapy. 105 Interestingly, 2 patients became pregnant while on hydroxyurea and delivered normally, without any congenital malformations in the infants.…”
Section: Safety Of Hydroxyurea In B-thalassemia Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…67,74,104 No renal or hepatic side effects were reported with hydroxyurea therapy. 67,69,71,74,75,82,85 Although some reports suggested that hydroxyurea may adversely affect gonadal function, 87 others failed to document such an association even on long-term therapy. 105 Interestingly, 2 patients became pregnant while on hydroxyurea and delivered normally, without any congenital malformations in the infants.…”
Section: Safety Of Hydroxyurea In B-thalassemia Patientsmentioning
confidence: 99%
“…75 The rate of gastrointestinal adverse events ranged between 1% and 30%. 50,65,67,69,71,74,77,81 Some studies also reported dermatological (hyperpigmentation, alopecia, maculopapular rash, or facial erythema) 65,69 and neurological (headache or dizziness) 65,69 adverse events on long-term therapy, although others did not observe such symptoms or attributed them to other disease-related risk factors. 67,74,104 No renal or hepatic side effects were reported with hydroxyurea therapy.…”
Section: Safety Of Hydroxyurea In B-thalassemia Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Hydroxyurea (HU) is FDA approved for treatment of SCD patients and it is also widely used for β-thalassemia. [8][9][10][11][12] How HU induces HbF production is poorly understood. Mechanisms proposed for the induction of HbF by HU include rapid erythroid regeneration, increased erythropoietin (EPO) production, apoptosis, nitric oxide (NO) production, 13 increased guanylate cyclase activity 13 and activation of the p38 MAPK pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyurea is a pharmacological inductor of HbF that significantly increases Hb levels and reduces transfusion needs in patients with sickle cell disease [6,7]. Hydroxyurea is expected to benefit patients with thalassemia, as the increase in c-chain synthesis may decrease the imbalance between a and non-a chains.…”
Section: Introductionmentioning
confidence: 99%